2009
DOI: 10.1124/mol.109.055376
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones Mimic Glucose Starvation in Facilitating Sp1 Degradation through the Up-Regulation of β-Transducin Repeat-Containing Protein

Abstract: This study investigated the mechanism by which the transcription factor Sp1 is degraded in prostate cancer cells. We recently developed a thiazolidinedione derivative, (Z)-5-(4-hydroxy-3-trifluoromethylbenzylidene)-3-(1-methylcyclohexyl)-thiazolidine-2,4-dione (OSU-CG12), that induces Sp1 degradation in a manner paralleling that of glucose starvation. Based on our finding that thiazolidinediones suppress ␤-catenin and cyclin D1 by up-regulating the E3 ligase SCF ␤-TrCP , we hypothesized that ␤-transducin repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…4C) and HeLa cells (Supplementary Fig. S4C) by ciglitazone (CG), troglitazone (TG), or resveratrol (26,27) reduced Twist1 expression, supporting that β-TrCP upregulation mediates Twist1 degradation. A double thymidine (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…4C) and HeLa cells (Supplementary Fig. S4C) by ciglitazone (CG), troglitazone (TG), or resveratrol (26,27) reduced Twist1 expression, supporting that β-TrCP upregulation mediates Twist1 degradation. A double thymidine (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…However, studies have demonstrated that reduced O-glycosylation of Sp1 was associated with increased proteasome susceptibility and that a E3 ligase SCF (β-transducin repeat-containing protein) targeted Sp1 for proteasomal degradation in response to glucose starvation. 54,55 Therefore, different ubiquitin E3 ligases may modulate Sp1 stability under the different physical conditions; the detail mechanism needs further address. It is also interesting to note that no upshift bands were found in sumoylated Sp1 during mitosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ΔF-β-TrCP and ΔNT-β-TrCP were generated as previously described [13]. The resulting fragments were ligated into the pMyc4-CMV14 expression vector.…”
Section: Methodsmentioning
confidence: 99%